دور المعاملة بحمض الساليسيليك في إنتاجية ونوعية صنفي التبغ برلي وفرجينيا المعداة بفيروس البطاطا واي في سورية - خدام, مازن; سليم, راعي (Latakia University Journal -Biological Sciences Series, 2019)
أظهرت النتائج دور حمض الساليسيليك (SA) في زيادة إنتاجية وتحسين نوعية صنفي التبغ برلي وفرجينيا المعداة بفيروس البطاطا واي حقلياً، وذلك حسب تركيز الحمض وزمن إضافته قبل العدوى بالفيروس، وكانت أعلى إنتاجية وعلى صنفي التبغ برلي وفرجينيا من الأوراق الخضراء عند المعاملة بالحمض رياً بتركيز 0.5 Mm وعدوى بالفيروس بعد 3 أيام (8.605، 8.978 كغ) مقارنة بالشاهد السليم (8.233،9.187 كغ) والشاهد المعدى بدون معاملة بالحمض (4.130، 3.570 كغ) ومن الأوراق المجففة (1.370، 1.495 كغ) مقارنة بالشاهد السليم (1.080،1.583 كغ) والشاهد المعدى بدون معاملة بالحمض (0.516، 0.490 كغ)، وارتفعت نسبة المركبات الآزوتية عند الصنف برلي بشكل غير معنوي في جميع المعاملات ماعدا المعاملة بالحمض رياً بتركيز 0.75 mM وعدوى بالفيروس بعد 3 أيام وهي مؤشر سلبي لنوعية أوراق التبغ الجافة، وانخفضت نسبة البروتين عند معاملة الصنف برلي بالحمض رشاً بتركيز 0.5 mM ،0.75 mM وعدوى بالفيروس بعد 3 أيام إلى 9.8% وهي الأفضل، وكانت أعلى نسبة للسكريات عند المعاملة بالحمض تركيز 0.5 mM رياً وعدوى بعد يوم عند الصنف فرجينيا 9.1% مقارنة مع جميع المعاملات ماعدا المعاملة بالحمض رياً بدون عدوى وهي الأفضل. The Results showed the role of salicylic acid (SA) in increasing the productivity and quality of tobacco Burley and Verginia which inoculated with Potato y virus in the field. According to the concentration and time of applying SA before inoculation and the highest productivity of fresh and dry leaves at the treatment with SA drench 0.5 mM and inoculation with pvy 3 days (8.978, 8.605 kg) comparing healthy control (8.233, 9.187 kg) and inoculation control (3.570, 4.130 kg) and dry leaves (1.495, 1.370 kg) comparing healthy control (1.080, 1.583 kg) and inoculation control (0.490, 0.516 kg) and the ratio of NPN in Burley leaves without significant in all treatment increased except the treatment with SA drench 0.75mM and inoculation with pvy 3 daythatsignificant effect on quality of cured leaves, and the ratio of protein decreased at the treatment with sprays with SA at 0.5Mm and 0.75Mm concentration (9.8%) and it is the best result, and the highest ratio of sugars in Verginia at the treatment with SA 0.5mM concentration and inoculation with virus after day (9.1%) comparing in all treatment except the treatment using drench with SA without inoculation virus and it is also the best result.